PENGARUH PERTUMBUHAN EKONOMI, JUMLAH PENDUDUK, DAN PRODUKSI PADI TERHADAP JUMLAH KONSUMSI BERAS DI BALI - Yulianti, Rina; Sarifah, Sudati Nur (Jendela Inovasi Daerah, 2023)
Rice is a basic food requirement for the majority of Indonesians, especially those in the Province of Bali. Rice consumption rises year after year, but not in lockstep with rice output. The goal of this study is to look at the factors that influence rice consumption in the Province of Bali. The purpose of this study is to see how three independent variables affect the amount of rice consumption in Bali, with the independent variables being GRDP, Population, and Rice Production, both simultaneously and partially in the 2015-2019 time period. The results of this study indicate that the three independent variables have a positive and significant effect on rice consumption in the Province of Bali. It can be concluded that the variables of GRDP, Population, and Rice Production have an effect on Rice Consumption in the Province of Bali.